Infectious disease consultations in a Japanese tertiary care teaching hospital: a retrospective review of 508 cases - Yoshiro Hadano; Takanori Matsumoto (BMC, 2018)
Abstract Objective Limited epidemiological data are available at tertiary care teaching hospitals in Japan. We reviewed infectious disease (ID) consultations in a tertiary acute care teaching hospital in Japan. Methods This is a retrospective review of the ID consultations from October 2016 to December 2017. The demographic data, such as requesting department, consultation wards, and final diagnosis, were analyzed. Results There were 508 ID consultations during the 15-month study period. Among the 508 consultations, 201 cases (39.6%) were requested from the internal medicine department and 307 cases (60.4%) were requested from departments other than internal medicine. The most frequent requesting departments were Surgery (n = 102, 20.1%), Pulmonary Medicine (n = 41, 8.1%), and Plastic Surgery (n = 35, 6.7%). The most common diagnoses were intra-abdominal (n = 81, 16.0%), respiratory (n = 62, 12.2%), and skin and soft tissue infections (n = 59, 11.6%). ID consultations for disease diagnosis and management were more frequent in the internal medicine group than in the non-internal medicine group (37 cases, 20.8% vs. 40 cases, 13.7%, p = 0.046), and the number of requests for consultations for noninfectious diseases at the time of final diagnosis was higher in the internal medicine group than in the non-internal medicine group (21 cases, 11.8% vs. 16 cases, 5.5%, p = 0.0153). Conclusion Some physicians prefer ID specialists to identify and solve various medical problems. Internists had a greater tendency to request consultations for diagnostic problems, and noninfectious disease specialists have more requests for consultation at the point of final diagnosis. The role of ID specialists is expanding, from individual patient management to antibiotic stewardship, antibiotic prophylaxis, and development of and adherence to antibiotic protocol implementation based on the hospital's microbial susceptibility and infection control. Although the number of specialists is limited in Japan, ID services now play an important role for achieving a good outcome in patient management.